2017
DOI: 10.1371/journal.pone.0181726
|View full text |Cite
|
Sign up to set email alerts
|

Increased ParB level affects expression of stress response, adaptation and virulence operons and potentiates repression of promoters adjacent to the high affinity binding sites parS3 and parS4 in Pseudomonas aeruginosa

Abstract: Similarly to its homologs in other bacteria, Pseudomonas aeruginosa partitioning protein ParB facilitates segregation of newly replicated chromosomes. Lack of ParB is not lethal but results in increased frequency of anucleate cells production, longer division time, cell elongation, altered colony morphology and defective swarming and swimming motility. Unlike in other bacteria, inactivation of parB leads to major changes of the transcriptome, suggesting that, directly or indirectly, ParB plays a role in regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 88 publications
2
32
0
Order By: Relevance
“…Since a lack of ParB in P. aeruginosa PAO1161 parB null mutant produced clear-cut effects under conditions of exponential growth in rich medium at 37°C, but not as severe as during growth in minimal medium (24, 76), such milder conditions were used for these experiments. The ChIP procedure was performed with PAO1161 (WT) strain, PAO1161 parB null mutant (negative control), and PAO1161/pKGB9 ( araC-araBAD p- parB ) strain (ParB+++) with 5-fold increased ParB level which does not retard bacterial growth (63). Additionally, three parS mutants were included: parS null with all ten parS sites mutated, parS1 - 4 mutant with the four high affinity ParB sites inactivated, and parS2 + strain with nine parS sequences modified and only parS2 left intact (59).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since a lack of ParB in P. aeruginosa PAO1161 parB null mutant produced clear-cut effects under conditions of exponential growth in rich medium at 37°C, but not as severe as during growth in minimal medium (24, 76), such milder conditions were used for these experiments. The ChIP procedure was performed with PAO1161 (WT) strain, PAO1161 parB null mutant (negative control), and PAO1161/pKGB9 ( araC-araBAD p- parB ) strain (ParB+++) with 5-fold increased ParB level which does not retard bacterial growth (63). Additionally, three parS mutants were included: parS null with all ten parS sites mutated, parS1 - 4 mutant with the four high affinity ParB sites inactivated, and parS2 + strain with nine parS sequences modified and only parS2 left intact (59).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that ParA, ParB and parS sequences are engaged in genome partitioning in many bacteria (9, 1223, 25, 31). Additionally, they have been shown to be involved, in a species-specific manner, in the regulation of DNA replication initiation by DnaA (14, 15), in the formation of a loading platform for SMC on newly replicated DNA to assure its proper condensation (46, 47), in positioning of oriC domains at defined cell locations (9, 12, 24, 25, 43, 44, 79), coordination of replication and cell division (18, 39, 80) but also in regulation of gene expression (53, 57, 63, 80).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the use of PAO1161 in conjugation experiments spontaneous rifampicin resistant clone was obtained 18 . The PAO1161 strain was used in studies on chromosome segregation and gene expression in P. aeruginosa using genome wide approaches [19][20][21] as well as in other physiological and genetic studies [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%